ANALISIS KAUSALITAS ANTARA BELANJA DAERAH DAN PENDAPATAN ASLI DAERAH DI PROVINSI KALIMANTAN TIMUR PADA TAHUN 2011-2024 - Angelika Sinania; Alexandra Hukom (CV. ADIBA AISHA AMIRA, 2024)
Regional autonomy is an improvement in welfare and services for the community that is carried out fairly, equitably, and in order to create a good relationship between one region and another. Local governments in East Kalimantan Province have rights and obligations in managing regional revenues and managing Regional Original Revenue. Regional expenditure aims to increase the development of various capital accommodations. Infrastructure development and accommodation are carried out to increase investment attractiveness. Infrastructure development has a real impact on the increase in Regional Original Income (PAD). This study is aimed at analyzing the causality between regional expenditure and local native income in East Kalimantan province in 2011-2024. The analytical methods used in this study are Cointegration Test, Unit Root Test and Granger Causality Test. From the results of data analysis, it shows that Regional Expenditure and Regional Original Income in East Kalimantan Province are fluctuating during the period 2011-2024. The results of the cointegration test analysis show that there is no long-term balance relationship between economic growth and external debt. Meanwhile, according to the results of the root test analysis, it is known that the variables Regional Expenditure and Regional Original Income are declared stationary. Then through the analysis of Granger's causality test showed that there was no significant effect of Regional Original Income (PAD) on Regional Expenditure (BD). From these two results, it can be concluded that there is no influence between Regional Original Income (PAD) and Regional Expenditure so that there is no significant influence between the two